La migración interregional en la novela a la costa de Luis A. Martínez - Sarango Guajala, Gloria Etelbina (2015)
Of the multiple criteria on migration, to guide the implementation of research on interregional migration in the novel A Coast Luis A. Martinez, noteworthy internal migration. In this case, the break with the place of origin seems radical in affective, economic and social ties, under these considerations, this study has the general objective : Identify and describe the causes and consequences of intraregional migration in the Sierra - Costa a novel Coast Luis A. Martinez. Several methods , which together guided this work degree, including analytic- synthetic method scientific method , the method of literary analysis proposed by Fernando Lázaro Carreter and Evaristo Correa, in his manual " is used As discussed a technical literature , the term literary analysis " text, and concludes that between structural causes in the novel to the coast of Luis A. Martinez, is the scarcity and declining employment ; however, within the cyclical causes the persistence of the cocoa boom of the twentieth century is evident , the constant search for better living conditions . Referring to the structural consequences of migration in Ecuador have, remittances, increased trade and declining poverty of families of migrants in the Amazon region. Among the short-term consequences can be seen in the study are family breakdown, cultural alienation , ancient customs and abuse and theft to outsiders. So we conclude that interregional migration appears as an escape to the various problems affecting human well- being